2014
DOI: 10.1037/a0036781
|View full text |Cite
|
Sign up to set email alerts
|

Predicting object features across saccades: Evidence from object recognition and visual search.

Abstract: When we move our eyes, we process objects in the visual field with different spatial resolution due to the nonhomogeneity of our visual system. In particular, peripheral objects are only coarsely represented, whereas they are represented with high acuity when foveated. To keep track of visual features of objects across eye movements, these changes in spatial resolution have to be taken into account. Here, we develop and test a new framework proposing a visual feature prediction mechanism based on past experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
148
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(163 citation statements)
references
References 94 publications
(159 reference statements)
13
148
1
1
Order By: Relevance
“…These findings reveal how eye movements reshape feature processing at the site of a saccade target, and could represent underlying mechanisms of presaccadic enhancement [14] and perceptual stability [43, 4547] reported in the literature, which illustrate functional benefits of the tight coupling between perception and movements.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These findings reveal how eye movements reshape feature processing at the site of a saccade target, and could represent underlying mechanisms of presaccadic enhancement [14] and perceptual stability [43, 4547] reported in the literature, which illustrate functional benefits of the tight coupling between perception and movements.…”
Section: Discussionmentioning
confidence: 72%
“…Human observers can maintain a stable percept of a saccade target by integrating its presaccadic (in the periphery) and postsaccadic (at the fovea) representations of both SF [45] and orientation [46, 47]. The tuning modulations we found suggest that saccade preparation modifies the representation of the saccade target to be more fovea-like –i.e., higher resolution and finer orientation tuning– just before saccade onset.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, although both rely on an action at distance, social agency has a communicative function, whereas physical agency has only a performative function, such as for example button switching in gaze-operated devices. However, there is a growing literature on the different effects of saccadic eye movements suggesting that similar associative and predictive mechanisms may govern the acquisition and usage of social and non-social effects of eye movements [4,23,24,61]. It is therefore entirely possible that, similarly to other behaviors and traits (e.g., [62,63]), also gaze agency can take advantage of existing neural mechanisms to implement a new function.…”
Section: Discussionmentioning
confidence: 99%
“…This finding pointed to a failure of low-level sensori-motor mechanism in charge to compensate the sensory consequences of one’s own movements in schizophrenia [22]. More recently, other studies addressed the relation between saccades and their visual effects [23,24], thus further stressing the importance of proper sensori-motor contingencies in visual perception and action [25]. For example, in a recent study [26] observers were shown two different faces concurrently presented in the left and right sides of the visual field, and a tone paired with a given ocular action (i.e., making a spontaneous rightward or leftward saccade to one of the two faces).…”
Section: Introductionmentioning
confidence: 99%
“…When a potential target attracts our attention, we typically saccade to it (Herwig & Schneider, 2014). In general, we found parallel attention effects for keypress RT and saccade latency.…”
Section: Discussionmentioning
confidence: 99%